POSTERIOR AND ANTERIOR BILATERAL CROSS BITE CORRECTION IN DECIDUOUS DENTITION WHITH ADHESIVE REMOVABLE ApPUANCE. A CASE REPORT - Soldevilla Galarza, Luciano Carlos (2004)
We reporte a cros~bite clinic case involving the use of a rigid acrylic-bonded palatal expansion appliance. The proposed design modifications allow the expansion appliance to be used in patients of any dental age and overall in the cross bite correction in the early deciduous dentition. The treatment plan and objectives were to expand the maxilla, elimina te the functional shift and posterior and anterior crossbite correction.